2010
DOI: 10.3233/jad-2010-100348
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Pathobiology in Parkinson's Disease and Amyotrophic Lateral Sclerosis

Abstract: Abstract. Parkinson's disease (PD) and amyotrophic lateral sclerosis (ALS) are the second and third most common human adult-onset neurodegenerative diseases, respectively, after Alzheimer's disease. They are characterized by prominent age-related neurodegeneration in selectively vulnerable neural systems. Some forms of PD and ALS are inherited, and genes causing these diseases have been identified. Morphological, biochemical, and genetic, as well as cell and animal model, studies reveal that mitochondria could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 204 publications
0
19
0
1
Order By: Relevance
“…This hypothesis is based on several well established observations in the literature: (1) Dysregulation of mitochondrial homeostasis has been implicated in ageing and a number of age-related diseases [12,64,65]. (2) A number of large scale proteomic studies have shown that mitochondrial proteins are highly acylated [29,43,6668].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is based on several well established observations in the literature: (1) Dysregulation of mitochondrial homeostasis has been implicated in ageing and a number of age-related diseases [12,64,65]. (2) A number of large scale proteomic studies have shown that mitochondrial proteins are highly acylated [29,43,6668].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction and oxidative stress are well-documented in PD; in particular, mitochondria in complex I have been found to be defective in both familial and sporadic PD (Lin and Beal, 2006; Matsuda et al, 2010; Martin, 2006, 2010; Chu and Zhe, 2010; Cookson, 2010; Morais et al, 2009; Lin et al 2009). With the focus on abnormal mitochondrial dynamics, little research attention has been paid to elucidating the involvement of Drp1 and mitochondrial fission and fusion imbalance in PTEN induced putative kinase 1 (PINK1) and parkin mutants of fruitflies and mouse models.…”
Section: Drp1 and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In ALS, mitochondrial abnormalities have been extensively described in both familial and sporadic ALS patients and also in transgenic mouse models generated with mutant SOD1 (Magrane and Manfredi 2009 2010; Zhou et al 2009, Kawamata et al 2008, Cassina et al 2008, Ilieva et al 2007, Martin 2006, 2009, 2010, Martin et al 2009, Raimondi et al 2006, Krasnianski et al 2005, Kirkinezos et al 2005, Zhu et al 2002, Dhaliwal and Grewal 2000). Histopathological research revealed that mitochondria may be targets of toxicity in ALS since vacuolated and dilated mitochondria with disorganized cristae and membranes in motor neurons have been observed in patients with ALS (Reddy and Reddy, 2010), and mitochondrial defects (e.g., impaired respiration and increased uncoupling proteins) have been reported in the spinal cords and muscle biopsies of patients with ALS.…”
Section: Drp1 and Neurodegenerative Diseasesmentioning
confidence: 99%
“…The opening of mitochondrial permeability transition pore (mPTP) is central to mitochondrial structure and function, including reactive oxygen species (ROS) production. A mutation in the mitochondrial gene PTEN-induced kinase 1 leads to selective opening of the mPTP (Gautier et al, 2012), and the pharmacological agent rasagiline, which is prescribed to PD patients, exerts its effect in part through the mPTP (Youdim et al, 2005), indicating that changes in mPTP opening can be a causal factor in PD (Martin, 2010;Mashayekhi et al, 2014). These findings also suggest that the mPTP could serve as a viable drug target (Penna et al, 2013;Rao et al, 2013).…”
Section: Introductionmentioning
confidence: 89%